Coracohumeral Ligament Sectioning in Teres Major versus Latissimus Dorsi Tendon Transfer in Brachial Plexus Birth Palsy - Gutierrez-Pereira, Javier; Garcia-Lopez, Antonio (Journal of Brachial Plexus and Peripheral Nerve Injury, 2025)
The latissimus dorsi tendon transfer (LDTT) to the supraspinatus tendon is a common procedure for restoring shoulder abduction and external rotation in upper root brachial plexus lesions. However, its association with scapular retraction often limits shoulder abduction.This retrospective study compared the functional outcomes of teres major tendon transfer (TMTT) combined with anterior coracohumeral ligament release (CHLR) versus LDTT. Patients who underwent surgery at our center between January 2012 and December 2022 were included, with a mean follow-up of 38 months. Outcomes were assessed using a range of motion and the Mallet scale.A total of 40 patients were included, with 20 undergoing TMTT with CHLR and 20 undergoing LDTT. The overall mean age was 3.9 years (range: 2.7–4.8), with mean ages of 3.4 years (range: 2.2–5.2) in the LDTT group and 4.1 years (range: 2.8–5.2) in the TMTT with the CHLR group. The TMTT with CHLR group achieved mean gains of +77 degrees in active abduction, +44 degrees in active external rotation, and +46 degrees in passive external rotation. In comparison, the LDTT group demonstrated gains of +46, +27, and +24 degrees, respectively, for the same parameters.TMTT combined with anterior CHLR significantly improves shoulder abduction and external rotation in patients with Brachial plexus birth injury, particularly those with internal rotation contractures. This technique offers superior functional outcomes compared to LDTT, suggesting a more effective therapeutic alternative.IV, retrospective comparative study.
Keywords: coracohumeral ligament; latissimus dorsi; brachial plexus birth injury; tendon transfer; teres major